Optimizing Insurance and Guarantees for Deceased Customers in Murabaha Financing: A Comprehensive Analysis - Muhammad Fahmul Iltiham; Nur Iva Apriliyah (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
This study concludes that the settlement process for insurance and guarantees in the event of a customer's death follows the established procedures of PT. BPRS Mojo Artho, Pandaan Branch. The process involves promptly reporting the customer's demise and subsequently submitting an insurance claim. If the claim is successful, the remaining debt is repaid, and the guarantee is returned. However, if the insurance claim is unsuccessful, the remaining debt must still be repaid by the customer's heirs, and the guarantee will be held as collateral. In cases where insurance claims fail, there are various factors contributing to the outcome, such as incomplete data or submissions that exceed the policy limit. It is important to note that such instances deviate from the principles of Sharia insurance, as the customer's lack of awareness about cooperation plays a role. However, the BPRS endeavors to assist in line with the principles of Sharia insurance by providing relief to the heirs, ensuring that the guarantee is not seized and auctioned off. _____________________________Studi ini menyimpulkan bahwa proses penyelesaian asuransi dan jaminan dalam kasus kematian nasabah mengikuti prosedur yang telah ditetapkan oleh PT. BPRS Mojo Artho, Cabang Pandaan. Proses tersebut melibatkan pelaporan segera atas kematian nasabah dan selanjutnya mengajukan klaim asuransi. Setelah semua data yang diperlukan disediakan, klaim asuransi diproses oleh perusahaan asuransi. Jika klaim berhasil, sisa hutang akan dibayar dan jaminan akan dikembalikan. Dalam kasus di mana klaim asuransi gagal, terdapat berbagai faktor yang berkontribusi terhadap hasilnya, seperti data yang tidak lengkap atau pengajuan yang melebihi batas kebijakan. Penting untuk dicatat bahwa kejadian semacam ini menyimpang dari prinsip asuransi syariah, karena kurangnya kesadaran nasabah tentang kerjasama berperan dalam hal ini. Namun, BPRS berupaya membantu sesuai dengan prinsip-prinsip asuransi syariah dengan memberikan bantuan kepada ahli waris, memastikan bahwa jaminan tidak disita dan dilelang.